Playful Virtual Violence An Ethnography of Emotional Practices in Video Games - Bareither, Christoph (Social Sciences, 2020)
Violence in video games has been a controversial object of public discourse for several decades. Building upon an extensive ethnographic study of players' emotional practices,this Element provides new insights into the complexity and pleasures of player experiences, contributing to societal and academic debate on a critical aspect of video gaming.